2001
DOI: 10.1002/app.1852.abs
|View full text |Cite
|
Sign up to set email alerts
|

Formation of antibiotic, biodegradable polymers by processing with Irgasan DP300R (triclosan) and its inclusion compound with β‐cyclodextrin

Abstract: The inclusion compound (IC) between the FDA‐approved antibacterial Irgasan DP300 (Trichlosan), and β‐cyclodextrin (CD) has been formed. When the Irgasan–β‐CD–IC is embedded in biodegradeable/bioabsorbable films of poly(ϵ‐caprolactone) (PCL) at low levels (a few wt %), they are rendered resistant to the growth of E. coli bacteria. When these same PCL films embedded with Irgasan–β‐CD–IC are used as the adhesive for laminating cotton fabrics, we observe the resulting cotton laminates to also be resistant to the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…In other studies (Chacon and others 2006a, 2006b; Li and others 2007), microencapsulated AIT was used to optimize the effectiveness of AIT. Microencapsulation is a well‐known procedure used to gradually release medicines (Lu and others 2001), and is used to stabilize or to trap flavor and odor (Li and others 2007). Moreover, controlled time‐releasing systems could theoretically contribute in reducing the amount of AIT necessary to achieve bactericidal effects since interfering glutathione, cysteine, and other sulphydryl compounds are lost during meat aging (Khan and Lentz 1977; Faustman and Cassens 1991).…”
Section: Resultsmentioning
confidence: 99%
“…In other studies (Chacon and others 2006a, 2006b; Li and others 2007), microencapsulated AIT was used to optimize the effectiveness of AIT. Microencapsulation is a well‐known procedure used to gradually release medicines (Lu and others 2001), and is used to stabilize or to trap flavor and odor (Li and others 2007). Moreover, controlled time‐releasing systems could theoretically contribute in reducing the amount of AIT necessary to achieve bactericidal effects since interfering glutathione, cysteine, and other sulphydryl compounds are lost during meat aging (Khan and Lentz 1977; Faustman and Cassens 1991).…”
Section: Resultsmentioning
confidence: 99%
“…The encapsulation of small guest molecules in CD cavities enhances their stability, and in addition, facilitates melt or solution processing, irrespective of the nature of the guest molecules. Our research group has shown successful encapsulation of various guest molecules (triclosan, neomycin sulfate, antiblaze RD-1, nonoxynol-9, and azo-dyes) and subsequent melt processing with polymers [ 52 , 53 , 54 , 55 , 56 ]. By employing such a methodology, not only can the stability and controlled release of the guest molecules be ensured, but it also facilitates the fabrication of facile commercial products containing small guest molecules [ 56 ].…”
Section: Cyclodextrin Functionalized Aliphatic Polyester Nanofibermentioning
confidence: 99%
“…Similar results were also reported by Tonelli et al, where TR/β-CD crystals incorporated in poly(ε-caprolactone) (PCL) films have shown improved effectiveness against E. coli when compared to PCL film with TR only. 43 This is possibly because of the enhanced solubility of TR into agar medium by CD-IC. It was also noted that the PLA/TR/β-CD-IC sample had better inhibition levels against both of the bacteria when compared to the PLA/TR/γ-CD-IC sample, and this may be caused by the presence of uncomplexed TR in the PLA/TR/β-CD-IC sample, which can be released readily at the initial stage.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%